APPROXIMATE ANALYTICAL EXPRESSIONS OF CONCENTRATION OF ACETIC ACID AND HYDROGEN PEROXIDE IN BATCH PHOTO-FENTON REACTION - RANI, J. FEMILA MERCY; MEENA, V.; GANESAN, S.; RAJENDRAN*, L. (International Journal of Mathematical Archive, 2018)
Mathematical model of the photo-Fenton oxidation process is discussed. This model involves a system of nonlinear equations containing a nonlinear term related to Eley-Rideal-type kinetics. Simple and closed- form of approximate analytical expressions of concentrations of acetic acid and hydrogen peroxide are reported. These analytical results are compared with available experimental and numerical (Matlab program) results. Satisfactory agreement is noted.